2017
DOI: 10.1093/clinid/cix249
|View full text |Cite
|
Sign up to set email alerts
|

Decreased azithromycin susceptibility of Neisseria gonorrhoeae isolates in patients recently treated with azithromycin

Abstract: The results suggest that frequent azithromycin use in populations at high risk of contracting N. gonorrhoeae induces an increase in MIC, and may result in resistance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
34
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(37 citation statements)
references
References 0 publications
1
34
2
Order By: Relevance
“…Our findings contrast partly with the only comparable epidemiological study on this topic, which found evidence of a linear association between days since azithromycin treatment and azithromycin MIC, among a subanalysis of 14 patients treated with azithromycin in the previous 30 days in an STI clinic in Amsterdam 11. Azithromycin MICs in that study were tested using the E-test method, which generates more MIC values than agar dilution (as used in our study); thus, it is possible that our data on azithromycin MIC were not fine-grained enough to identify a linear trend.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Our findings contrast partly with the only comparable epidemiological study on this topic, which found evidence of a linear association between days since azithromycin treatment and azithromycin MIC, among a subanalysis of 14 patients treated with azithromycin in the previous 30 days in an STI clinic in Amsterdam 11. Azithromycin MICs in that study were tested using the E-test method, which generates more MIC values than agar dilution (as used in our study); thus, it is possible that our data on azithromycin MIC were not fine-grained enough to identify a linear trend.…”
Section: Discussioncontrasting
confidence: 99%
“…However, even with our less detailed MIC data, we would expect to see some indication of a trend if an association existed in this setting. Analysis of other time frames in the Amsterdam study did not yield any associations, in line with our findings 11. Previously, GRASP and the European Gonococcal Antimicrobial Surveillance Programme have found associations between azithromycin resistance and previous NG infection;23 24 however, neither study was designed to test this specific hypothesis and lacked detailed information on exposure intervals.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…The variable tissue penetration of antibiotics into the pharynx, a site of gonococcal infections, is one likely source of resistance, as the dose needed to clear urethral or cervical infection may yield a relatively low pharyngeal antibiotic concentration inadequate for eradication and thereby promote resistance emergence. A recent epidemiological study relating annual antibiotic consumption and gonococcal resistance suggested that the pressure from bystander selection may be small to none, whereas a study from the Netherlands indicated that previous exposure to azithromycin is associated with higher levels of azithromycin resistance, perhaps reflecting the long half‐life of azithromycin and the observation that individuals previously infected with gonorrhea are at higher risk for subsequent infection …”
Section: Acquisition Of Antibiotic Resistancementioning
confidence: 99%
“…A recent epidemiological study relating annual antibiotic consumption and gonococcal resistance suggested that the pressure from bystander selection may be small to none, 27 whereas a study from the Netherlands indicated that previous exposure to azithromycin is associated with higher levels of azithromycin resistance, perhaps reflecting the long half-life of azithromycin and the observation that individuals previously infected with gonorrhea are at higher risk for subsequent infection. 28 In addition to de novo acquisition of resistance due to antibiotic exposure, genes and alleles can easily move between N. gonorrhoeae lineages, providing another mechanism for acquisition of antibiotic resistance. N. gonorrhoeae harbors several mobile genetic elements.…”
Section: Acquisition Of Antibiotic Resistancementioning
confidence: 99%